Valorising digestate as bio-based fertiliser next to biogas: Environmental life cycle costing of three farm-scale anaerobic co-digestion scenarios - Vikki, Karetta; Tampio, Elina; Winquist, Erika; Saarinen, Merja; Luostarinen, Sari (Elsevier, 2026)
Anaerobic digestion (AD) combines waste management with the production of renewable energy and recycled fertiliser products. Despite international targets to increase the recycling of nutrients for bio-based fertilisers (BBFs), there is a lack of studies assessing the environmental and economic impacts of the life cycle of digestate coming out of AD, and of associating the functional unit (FU) with the digestate, facilitating the comparability between mineral fertilisers. This study evaluated the environmental life cycle costs and climate impacts per FU of both biogas (MWh) and digestate (kg of soluble nitrogen) from feedstock procurement to the use on a farm (cradle-to-grave) which allowed comparison to purchased energy and mineral fertiliser. Three different farm-scale anaerobic digestion scenarios were studied utilizing slurry and different co-feedstocks. Results showed that biogas and digestate produced at farm had lower climate impacts and costs than the corresponding purchased products in all three scenarios. Valuing digestate as co-product decreased life cycle emissions of biogas by 24–29 %. Correspondingly, the carbon footprint of the digestate increased by 6–8% but was compensated by carbon sequestration potential when applied in soil. The NPV was positive for biogas and digestate product in all scenarios and highest for scenario utilising food industry side streams as co-feedstock. Monetising climate impacts increased the NPV of biogas and digestate because replaceable energy and mineral fertiliser had higher climate impacts. Product level analyses revealed different product-specific hot spots for biogas and digestate for targeted improvements in sustainability.
Keywords: biogas; digestate; climate impacts; environmental life cycle costing; life cycle assessment; life cycle costing